Critical Inconsistencies in Early Implementations of the Marine Strategy Framework Directive and Common Fisheries Policy Objectives Hamper Policy Synergies in Fostering the Sustainable Exploitation of Mediterranean Fisheries Resources - Raicevich, Saša; Battaglia, Pietro; Fortibuoni, Tomaso; Romeo, Teresa; Giovanardi, Otello; Andaloro, Franco (Frontiers in Marine Science, 2017)
The Marine Strategy Framework Directive (MSFD) aims to achieve “Good Environmental Status” (GES) in EU marine waters by 2020. This initiative started its first phase of implementation in 2012, when each member state defined the GES and environmental targets in relation to 11 descriptors and related indicators for 2020. In 2013, the EU Commission launched the reformed Common Fisheries Policy (CFP), which aims to achieve biomass levels capable of producing maximum sustainable yield (MSY) for all commercial stocks exploited in EU waters by 2020, as well as contribute to the achievement of GES. These two pieces of legislation are aligned since according to Descriptor 3 (commercial fish and shellfish), the MSFD requires reaching a healthy stock status with fishing mortality (F) and spawning stock biomass (SSB) compatible with the respective MSY reference limits for all commercial species by 2020. We investigated whether the two policies are effectively aligned in the Mediterranean Sea, an ecosystem where the vast majority of stocks show unsustainable exploitation. For this purpose, we assessed and compared the number and typology of stocks considered by the member states when assessing GES in relation to data on stocks potentially available according to the EU Data Collection Framework (DCF) and the proportion of landings they represented. The number of stocks considered by the member states per assessment area was uneven, ranging between 7 and 43, while the share of landings corresponding to the selected stocks ranged from 23% to 95%. A lack of coherence between GES definitions among the member states was also revealed, and environmental targets were less ambitious than MSFD and CFP requirements. This could possibly reduce the likelihood of achieving fishery sustainability in the Mediterranean by 2020. These conditions limited the envisaged synergies between the two policies and are discussed in consideration of the recent Commission Decision on criteria and methodological standards for GES.